Detecting consumers with low familiarity in country-of-origin research - Kuralt, Vesna (Akademija MM, 2015)
This research aims to detect the attitudes of consumers who are not familiar with the country of origin by studying the image of an unfamiliar country of origin. To the best of our knowledge, there are no studies of country-of-origin effect in the context of low familiarity. In order to detect such consumers, we have added the "I don't know" option to the Likert scale. This has enabled us to divide the respondents into two groups according to their familiarity with the target country, which is an unfamiliar country of origin. Since this pre-assumes a considerable lack of consumer knowledge, we based our model on their emotions. For this reason, we referred to consumer affinity research when building the model of unfamiliar country of origin effect. An indirect impact of consumer affinity on their willingness to buy was fully mediated by perceived risk in both groups of consumers with high and low familiarity. Hence, we encourage researchers to include perceived risk in their study design.
Keywords: izvor blaga; kupci; potrošniki